Design and experiment for a numerical control nanosecond water-jet-guided laser processing test bench - Yang, Chunmei; Deng, Zhaojun; Feng, Li; Jiang, Xinbo; Guo, Can; Ma, Yan (Bioresources, 2019)
The laser processing method was applied to wood processing, and the water-jet-guided laser processing was adopted to design a numerical control nanosecond water-jet-guided laser processing test bench, which will provide a new theory and method for laser-processing wood. The numerical control nanosecond water-jet-guided laser processing test bench was built. Pinus sylvestris was used as the test subject. Laser energy, cutting speed, and defocus amount were used as the experimental factors. The aspect ratio was used as a response indicator. A three-factor, three-level Box-Behnken design was studied. A regression model of the three factors and aspect ratio was established. The test results showed that laser energy and cutting speed were the significant effects (p < 0.001) and that defocus amount was the notable effect (p < 0.05). The interaction of laser energy × cutting speed and laser energy × defocus amount had a significant effect on the aspect ratio. The optimal processing parameters were as follows: laser energy of 195.24 mJ, cutting speed of 1.03 mm/s, and defocus amount of -0.69 mm. The authors compared the surface of nanosecond water-jet-guided laser processing with the surface of laser processing. The former had little slag, and the cutting processing was stable. Therefore, nanosecond water-jet-guided laser processing showed better processing quality.